Unveiling the Anticancer Efficacy of Kaempferol from Moringa oleifera Against Breast Cancer: Insights from an In Silico Investigation - Maharani Retna Duhita; Vina Virlana Azhar (Universitas Sebelas Maret, 2026)
Breast cancer is a significant global health problem that is often encountered in women. Kaempferol from Moringa is known to control breast cancer cells. This study explores the in silico potential of kaempferol compounds derived from Moringa oleifera as breast cancer drug candidates. The results showed that kaempferol compounds have anticarcinogenic potential, with a high Pa value of 0.715, via the target proteins CYP1B1 and HSD17B2. The prediction of physicochemical properties indicates that kaempferol is a viable oral medication candidate, as it adheres to Lipinski's rule of five. However, it is dangerous if swallowed because it is classified as toxicity class 5. Molecular docking analysis indicates that kaempferol has high affinity for the target proteins CYP1B1 and HSD17B2. It can significantly contribute to breast cancer progression, with binding energies of -7.1 kcal/mol and -6.8 kcal/mol, respectively. Hydrogen bonds and hydrophobic interactions predominated the molecular interactions between kaempferol and the target proteins. These findings suggest that kaempferol from Moringa oleifera is a promising lead compound for the development of breast cancer treatments. Despite its potential, further studies are required to mitigate its toxicity risks, as indicated by the pharmacokinetics, drug-likeness, and toxicity assessments.